Databases and information systems IX selected papers from the Twelfth International Baltic Conference, DB&amp ; IS 2016 - Arnicans, Guntis (Frontiers in artificial intelligence and applications, 2016)
Databases and information systems are now indispensable for the daytoday functioning of businesses and society.